Emanuel Marx (1927–2022) - Levy, Thomas Evan (The Biblical archaeology review, 2022)
Emanuel Marx, Israeli anthropologist and expert on Bedouin societies, passed away on February 13, 2022; he was 94. Marx earned his master’s degree in Middle East history at the Hebrew University. In 1959, a scholarship enabled Marx to study for a Ph.D. at the University of Manchester in England. His dissertation, which focused on […]